Referentni deterministički model obostrano usmjerenog radiokanala : doktorski rad - Katalinić Mucalo, Ana 1980; Zentner, Radovan (Zagreb : A. Katalinić Mucalo ; Fakultet elektrotehnike i računarstva, 2013)
SAŽETAK: Referentni modeli radiokanala jedan su od ključnih elemenata za razvoj novih bežičnih sustava. Njihova je osnovna svrha dati uvid u svojstva radiokanala za neki specifični scenarij, kako bi se mogli koristiti kao platforma za ispitivanje, usporedbu i provjeru naprednih sustava koji koriste MIMO sučelje. Postojeći referentni modeli uglavnom su stohastički, definirani parametrima dobivenim statističkom obradom izmjerenih ili simuliranih podataka. Zbog svog stohastičkog karaktera, ovako dobiveni radiokanali mogu dati potpuno pogrešnu sliku radiokanala u nekom scenariju. Disertacija predlaže drugačiji pristup i definira koncept determinističkog referentnog modela radiokanala, koji se temelji na izvornim podacima. Format je osmišljen kao baza podataka pohranjenih radiokanala dobivenih rigoroznim trodimenzionalnim simulacijama metodom praćenja zrake, uz otvoreno sučelje preko kojeg bi se baza podataka mogla stalno nadograđivati novim radiokanalima dobivenim iz stvarnih terenskih mjerenja ili simulacija stvarnih fizičkih okolina metodom slijeđenja zrake. Kao podloga predloženom konceptu, napravljena je karakterizacija prostorne promjene radiokanala zbog kontinuirane promjene virtualnog izvora u slučaju difrakcije te definiran način modeliranja područja stacionarnosti u kojima su uvjeti u radiokanalu stalni. Osmišljeni koncept temelji se na novom parametru, entitetu zrake, kojim je omogućeno jednostavno praćenje zrake u mobilnom radiokanalu, uz značajno smanjenje računalne složenosti. - KLJUČNE RIJEČI: referentni model radiokanala, deterministički referentni model radiokanala, obostrano usmjereni model radiokanala, entitet zrake, područje vidljivosti, područje stacionarnosti, metoda praćenja zrake, interpolacija, urbani scenarij, difrakcija
SUMMARY: Reference channel models are one of the key elements for the development of new wireless systems. Their main purpose is to give an insight into radio channel properties of a specific scenario, in order for the model to become a platform for testing, comparison and verification of advanced systems with MIMO air interface. Existing reference channel models are mainly stochastic, defined by parameters obtained from statistical processing of original measured or simulated data. However, due to their stochastic nature, randomly generated radio channels might give a completely misleading representation of the specific scenario. This thesis proposes a different approach and defines the concept of deterministic reference channel model based on the usage of original, raw data, in a form of a large database of previously recorded real radio channels obtained from rigorous 3D ray-tracing simulations, with the possibility for upgrading the database with new measured and/or simulated radio channels through an open-source interface. As the background of the proposed concept, the thesis provides a spatial characterization of the dynamics of multipath due to the continuous virtual source movement in the case of diffraction. The proposed concept is based on a new parameter, ray entity, which enables continuous tracking of a mobile station in a radio channel, with a significant computational complexity reduction. The thesis is organized in five chapters. The first chapter gives an overview of basic terms related to the propagation of electromagnetic wave, as well as the main characteristics of MIMO systems, which are recognised as the standard for future wireless networks. The chapter addresses typical phenomena in the multipath environment, with the special focus on the phenomena caused by the movement of a mobile station in a radio channel. In order to fully exploit MIMO potential it is necessary to obtain detailed radio channel information, including the information about directions of departure and arrival for all multipath components, which allows optimized transmission and radio channel usage. The chapter also describes the double directional radio channel model, which contains the required data. The second chapter gives an overview of existing reference channel models. The chapter discusses various approaches in reference channel modelling, namely the difference between stochastic and deterministic approach, as well as problems regarding the parameterization for stochastic reference channel models. The focus is put on COST models, which define a significant number of parameters and describe many typical scenarios. Chapters 3-5 provide information about the conducted research and the contribution of the thesis. The analysis of specific phenomena was performed on data obtained by ray tracing simulations, as described in the third chapter. The simulations were run using an advanced 3D ray tracing tool developed at the University of Bologna by the group of Professor Vittorio Degli-Esposti. The chapter contains definitions and the main functionalities of the tool. The results were used for the definition of new parameters, as thoroughly elaborated in chapters four and five. The fourth chapter gives the results of the study of the specific phenomena of the electromagnetic wave propagation in the urban scenario, where diffraction is the dominant mode of propagation. The dynamics of multipath in case when the mobile station moves has been explored. The chapter has two main parts – the first one describes relevant parameters, while the second one provides the results obtained from the simulations, thus giving an insight into reference values for some parameters. A new parameter has been introduced - ray entity. Ray entity is a group of all rays which have the same origin and the same interaction types, in the same order. The virtual source of the ray entity is fixed in case of the reflection, but changes continuously as the mobile station moves in case of the diffraction. By defining the visibility areas in which certain ray entity is visible or not, stationary regions are also defined as a part of the mobile station route where all rays have a fixed virtual source. The concept of ray entity allows interpolation of the results, and allows modelling arbitrary movements of the mobile station. The chapter ends with the comparison of the results and the assessment of the existing parameters available in the literature. In the last, fifth chapter a new concept of deterministic radio channel model is introduced. The main benefit of the deterministic approach, when compared to the stochastic one, is the fact that it is based on exact and accurate data obtained by either measurements or rigorous simulations. The main drawback for its practical realization lies in the high computational requirements, including huge storage capacities and sophisticated, fast processors. The thesisproposes realization of deterministic radio channel model in a form of the database of exact realizations of double directional radio channels obtained from ray tracing simulations. The proposed solution is based on describing and storing ray entities, with the possibility of interpolating data with arbitrary resolution, which allows implementing mobility in the model, with negligible increase of computational complexity. Concluding remarks summarize the contribution of the thesis – the introduction of ray entity as a feasible deterministic reference channel model with the possibility for continuous mobile station tracking and reduced computational complexity. KEYWORDS: reference channel model, deterministic reference channel model, double directional radio channel, ray entity, visibility region, stationary region, ray-tracing, interpolation, urban scenario, diffraction
Na spor. naslv. str. naslov na eng.: Reference deterministic model of double directional radio channel : doctoral thesis
Bibliografija: str. 116-125. - Biografija [na hrv. i eng. jeziku]: str. 126 i str. 129. - Popis [autoričinih] radova [na hrv. i eng. jeziku]: str. 127-128 i str. 130-131